Pelabelan Harmonis Ganjil pada Graf Ular Jaring Berlipat - Fery Firmansah (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2020)
Graphs that have odd harmonious labeling properties are called odd harmonious graphs. The purpose of this study to obtain a new graph class construction with its properties, but also to prove that the new graph class has odd harmonious labeling properties. The research  method  used  consisted  of  several  steps  namely  data  research  preparations, research  investigations and  verification  of results. The  results  of  this study,  we  will provide a construction of a new graph class, that is, the pleated net snake graph and its properties.  Furthermore,  it  will  be  proven  that  the  pleated  net  snake  graph  has  odd harmonious labeling properties, so that the pleated net snake graph is an odd harmonious graph.